Strengthening Indonesia's Nickel Downstream Industry through Green Energy-Based Smelter Technology (Jurnal Pengelolaan Lingkungan Pertambangan, 2025)
Indonesia holds the world's largest nickel reserves, estimated at 55 million tons in 2024, making it a key player in the global nickel industry. The government has enacted downstream policies, such as a ban on raw ore exports and mandated domestic processing through Ministerial Decree of Energy and Mineral Resources (ESDM) No. 17 of 2020, to maximize its potential. These policies have accelerated the development of green energy-based smelters, which aim to enhance value addition while reducing environmental impacts like carbon emissions and hazardous waste. This study explores the current conditions and future prospects of developing nickel smelters in Indonesia, focusing on the policies in place, their economic impacts, and the role of green technologies in supporting smelter development initiatives. It highlights the economic, environmental, and social benefits of green technologies in Indonesia's nickel downstream industry. Innovations such as nanotechnology, Chemical Mechanical Polishing (CMP), bioleaching, and High-Pressure Acid Leach (HPAL) show significant potential by reducing emissions, waste, and energy consumption. PT Vale Indonesia, a leading player in the industry, exemplifies this transformation through initiatives like fuel shifting, renewable energy utilization, electrification of equipment, and energy efficiency measures. Despite challenges like high costs, infrastructure limitations, and waste management issues, green smelters substantially contribute to job creation, competitiveness, and environmental preservation. Continued policy support and cross-sector collaboration are crucial. However, it's the investment in research that holds the key to overcoming these barriers and positioning Indonesia as a global leader in sustainable nickel production